7(x+2)=8-5(x-7)

Simple and best practice solution for 7(x+2)=8-5(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+2)=8-5(x-7) equation:


Simplifying
7(x + 2) = 8 + -5(x + -7)

Reorder the terms:
7(2 + x) = 8 + -5(x + -7)
(2 * 7 + x * 7) = 8 + -5(x + -7)
(14 + 7x) = 8 + -5(x + -7)

Reorder the terms:
14 + 7x = 8 + -5(-7 + x)
14 + 7x = 8 + (-7 * -5 + x * -5)
14 + 7x = 8 + (35 + -5x)

Combine like terms: 8 + 35 = 43
14 + 7x = 43 + -5x

Solving
14 + 7x = 43 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
14 + 7x + 5x = 43 + -5x + 5x

Combine like terms: 7x + 5x = 12x
14 + 12x = 43 + -5x + 5x

Combine like terms: -5x + 5x = 0
14 + 12x = 43 + 0
14 + 12x = 43

Add '-14' to each side of the equation.
14 + -14 + 12x = 43 + -14

Combine like terms: 14 + -14 = 0
0 + 12x = 43 + -14
12x = 43 + -14

Combine like terms: 43 + -14 = 29
12x = 29

Divide each side by '12'.
x = 2.416666667

Simplifying
x = 2.416666667

See similar equations:

| 8l+8-l=9-8 | | 3x-2x+10=10+5x-40 | | 4x+2=8-2x | | C^3-216=y | | 3(-7-6x)-8=37+4x | | 5+2x=7(x+2)-6(x-2) | | x^2+21x+59=0 | | -(3-m)=-(4m+3) | | 100/566=1/9 | | -(x+1)+2=2x+1-3x | | 3(x+2)=9x+3-6x+3 | | 900/566= | | 10x-9=21+2x+3x | | -7a-(-2b)= | | k*36=8 | | -2(t-5)+9t=3t-4 | | 4(x-2)=8x-6-4x | | 4x^2-64x-69=0 | | 9z+3-5z=7+3z+4 | | 5xb=20 | | -1(-10)= | | 3.2q-1.8-5.4q=-3.2q-2.4 | | 15x-7=45x+11 | | 18-5m=3m-2m | | -6a^2-5a+21=0 | | 7x=30 | | 7x+5x+3+8=7x+4+4x | | 5x=-4x+18 | | 6x+3=3(x+5) | | 25m^2+20m-108=0 | | 2x+0=10 | | x-y=14 |

Equations solver categories